The role of obedience and the rule of law during the pandemic - Cem Çakmaklı; Selva Demiralp; Sevcan Yeşiltaş; Muhammed Ali Yıldırım (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
Despite the mounting costs of the pandemic at the global scale, the country-specific costs were rather heterogenous. National performances varied depending on the restrictive measures adopted, institutional strength, as well as adherence to stringency measures. We illustrate that obedience and rule of law strengthen the performance of the containment measures.
Keywords: I00; C33; E71; Z1; 330; COVID-19; Stringency; Obedience; Rule of Law